Propensity-matched analysis of the influence of perioperative statin therapy on outcomes after liver resection. Issue 4 (12th March 2019) - Dasari, B V M; Pathanki, A; Hodson, J; Roberts, K J; Marudanayagam, R; Mirza, D F; Isaac, J; Sutcliffe, R P; Muiesan, P
Abstract: Background: Perioperative use of statins is reported to improve postoperative outcomes after cardiac and non-cardiovascular surgery. The aim of this study was to investigate the influence of statins on postoperative outcomes including complications of grade IIIa and above, posthepatectomy liver failure (PHLF), and 90-day mortality rates after liver resection. Methods: Patients who underwent hepatectomy between 2013 and 2017 were reviewed to identify statin users and non-users (controls). Propensity matching was conducted for age, BMI, type of surgery and preoperative co-morbidities to compare subgroups. Univariable and multivariable analyses were performed for the following outcomes: 90-day mortality, significant postoperative complications and PHLF. Results: Of 890 patients who had liver resection during the study period, 162 (18·2 per cent) were taking perioperative statins. Propensity analysis selected two matched groups, each comprising 154 patients. Overall, 81 patients (9·1 per cent) developed complications of grade IIIa or above, and the 90-day mortality rate was 3·4 per cent (30 patients), with no statistically significant difference when the groups were compared before and after matching. The rate of PHLF was significantly lower in patients on perioperative statins than in those not taking statins (10·5 versus 17·3 per cent respectively; P = 0·033); similar results were found after propensity matching (10·4 versus 20·8 per cent respectively; P = 0·026). Conclusion: The rate of PHLF was significantly lower in patients taking perioperative statins, but there was no statistically significant difference in severe complications and mortality rates. Graphical Abstract: Perioperative use of statins had a protective effect on the incidence of posthepatectomy liver failure but did not influence other outcomes in patients undergoing liver resection. Statin use to prevent liver failure in HPB surgery